Synovial membrane immunohistology in early-untreated rheumatoid arthritis reveals high expression of catabolic bone markers that is modulated by methotrexate - Revu, Shankar (BioMed Central, 2013)
INTRODUCTION: We aimed to investigate the expression and therapeutic modulation of the receptor activator of the NF-κB ligand (RANKL) system in early-untreated rheumatoid arthritis (RA). METHODS: In this study, 15 patients with newly diagnosed RA (median symptom duration 7 months) were started on methotrexate (MTX) 20 mg weekly. Synovial biopsies were obtained by needle arthroscopy at baseline and 8 weeks after initiation of therapy. X-rays of the hands and feet were obtained at baseline and 1 year after diagnosis. Immunohistochemistry was performed to detect RANKL, receptor activator of nuclear factor-κB (RANK) and osteoprotegerin (OPG) in the synovial biopsies. The in vitro effect of MTX was tested on RA-derived primary fibroblasts and the osteoblasts-like osteosarcoma cell line (rtPCR, Western blot and ELISA) and in osteoclasts (tartrate-resistant acid phosphatase staining and dentine pit formation assay). RESULTS: MTX decreased synovial cellularity as well as RANK expression and the RANKL/OPG ratio. We confirmed this effect by a decrease of the mRNA and protein RANKL/OPG ratio in synovial-derived fibroblasts and osteoblasts-like tumoral cells exposed in vitro to methotrexate. Supernatants from MTX treated osteoblasts-like tumoral cells prevented pre-osteoclast formation in the absence of exogenous RANKL. Furthermore, MTX blocked osteoclastogenesis from peripheral blood mononuclear cells despite the presence of macrophage colony stimulating factor and RANKL, which indicates that MTX directly inhibits osteoclastogenesis. CONCLUSIONS: The synovial membrane of early-untreated RA is characterized by a high RANKL/OPG ratio that can be reversed by methotrexate.